A new parallel resonant DC link for soft switching inverters - Obdan, H; Bodur, H; Aksoy, I; Bekiroglu, N; Yildirmaz, G (TAYLOR & FRANCIS INC, 2005)
In this article, a new parallel resonant DC link (PRDCL) that provides soft switching (SS) and pulse width modulated (PWM) operation for inverters is presented. The new PRDCL ensures zero crossings for a time period, and at any time required for SS and PWM operation of the inverters, respectively. Moreover, the proposed PRDCL is realized by using only one auxiliary active switch, has a simple structure and ease of control, and operates under SS conditions. All switches in the soft switching inverters (SSI) equipped with the new PRDCL operate with soft switching, and are subjected to no additional voltage and current stresses. A detailed steady-state analysis of the proposed PRDCL is presented, and this theoretical analysis is verified by a prototype of a 250 V, 50 kHz and 1250 W circuit.
Keywords: parallel resonant DC link; PWM inverter; soft switching; soft switching inverter; VOLTAGE-SOURCE CONVERTERS; MOTOR-DRIVES; TOPOLOGY; Engineering